Risk Assessment in Pulmonary Arterial Hypertension According to Right Atrial Pressure and Correlation Between Mean Pulmonary Arterial Pressure with Right Atrial Pressure in Uncorrected Atrial Septal Defect Patients at Dr. Sardjito General Hospital - Krisnawati D., et al (ACI (Acta Cardiologia Indonesiana), 2017)
Risk Assessment in Pulmonary Arterial Hypertension According to Right Atrial Pressure and Correlation Between Mean Pulmonary Arterial Pressure with Right Atrial Pressure in Uncorrected Atrial Septal Defect Patients at Dr. Sardjito General Hospital